2005
DOI: 10.1080/0963818042000279713
|View full text |Cite
|
Sign up to set email alerts
|

The explanatory factors of intellectual capital disclosure to financial analysts

Abstract: The objective of this paper is to assess the information dealing with intellectual capital that firms disclose in presentations to sell-side analysts and the influences on these disclosures. Analysis of a sample of 257 reports from listed Spanish companies for 2000-2001 shows differences in disclosure levels by categories of intellectual capital. Companies usually report information regarding strategy, customers, and processes; information about research, development, and innovation is less often reported to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
175
5
29

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(233 citation statements)
references
References 45 publications
24
175
5
29
Order By: Relevance
“…Previous literature has examined the separate effects of resource attribute on intangible asset disclosure (Archambault & Archambault, 2003;Citron, Holden, Selim, & Oehlcke, 2005), the role of such disclosures as signals (Bozzolan, Favotto, & Ricceri, 2003;Garcia-Meca, Parra, Martinez, & Larran, 2005) and the role of governance factors such as board composition on disclosure (Haniffa & Cooke, 2002;Lufti, 1989, Malone, Fries, & Jones, 1993. Taken together the results of these and other studies suggest that investment in intangible resource and their disclosure through transparent governance structures are potential mechanisms to secure competitive advantage and its corollary of superior returns to shareholders.…”
Section: Intangible Assets -A Key Source Of Competitive Advantagesupporting
confidence: 59%
“…Previous literature has examined the separate effects of resource attribute on intangible asset disclosure (Archambault & Archambault, 2003;Citron, Holden, Selim, & Oehlcke, 2005), the role of such disclosures as signals (Bozzolan, Favotto, & Ricceri, 2003;Garcia-Meca, Parra, Martinez, & Larran, 2005) and the role of governance factors such as board composition on disclosure (Haniffa & Cooke, 2002;Lufti, 1989, Malone, Fries, & Jones, 1993. Taken together the results of these and other studies suggest that investment in intangible resource and their disclosure through transparent governance structures are potential mechanisms to secure competitive advantage and its corollary of superior returns to shareholders.…”
Section: Intangible Assets -A Key Source Of Competitive Advantagesupporting
confidence: 59%
“…This corroborates the results of Guthrie et al (2006) and Wong and Gardner (2005), concerning ICD, in Australia and New Zealand and it is inconsistent with the conclusions of Williams (2001), Woodcock andWhiting (2009), Oliveira et al (2006) and Garcia-Meca et al (2005). Li et al (2008) confirm that these inconclusive findings "could be due to the lack of representativeness in sampling at sector level".…”
Section: Discussioncontrasting
confidence: 44%
“…Some studies have indicated that companies, in Spain and Singapore, disclosure more intellectual capital information to signal to the market their real value and growth potential (Garcia-Meca et al, 2005;Williams & Firer, 2003), while other studies have showed no relationship at all (Williams, 2001). …”
Section: Voluntary Scd According Shareholder's Approach: the Argumentmentioning
confidence: 99%
“…A plethora of ICD studies have been conducted in many parts of the world examining disclosure of HC in company annual reports (Abeysekera & Guthrie, 2005;April, Bosma & Deglon, 2003;Arvidsson, 2003;Bergamini & Zambon, 2002;Bozzolan, Favotto & Ricceri, 2003;Brennan, 2001;Carnaghan, 1999;Firer & Williams, 2005;Flöstrand & Ström, 2006;Goh & Lim, 2004;Guthrie, Petty, Ferrier & Wells, 1999;Olsson, 2001;Petty & Cuganesan, 2005;Vandemaele, Vergauwen & Smits, 2005;Williams, 2001), IPO prospectuses (Bukh, Nielsen, Gormsen & Mouritsen, 2005;Nielsen et al, 2005), presentations to analysts García-Meca, Parra, Larrán & Martínez, 2005) and sell-side analysts reports (Arvidsson, 2003;Flöstrand, 2006;Flöstrand & Ström, 2006;García-Meca, 2005;Nielsen, 2004). In addition to HCD studies (Hedlin & Adolphson, 2000;Olsson, 2004;Subbarao & Zeghal, 1997), research on ICD in company annual reports and IPO prospectuses have evaluated the level of emphasis placed on HC disclosures by preparers of financial statements.…”
Section: Introductionmentioning
confidence: 99%